Rock Size‐Frequency Distributions at the InSight Landing Site, Mars. Issue 12 (20th December 2021) - Golombek, M. P.; Trussell, A.; Williams, N.; Charalambous, C.; Abarca, H.; Warner, N. H.; Deahn, M.; Trautman, M.; Crocco, R.; Grant, J. A.; Hauber, E.; Deen, R.
Abstract: Rocks around the InSight lander were measured in lander orthoimages of the near field (<10 m), in panoramas of the far field (<40 m), and in a high‐resolution orbital image around the lander (1 km 2 ). The cumulative fractional area versus diameter size‐frequency distributions for four areas in the near field fall on exponential model curves used for estimating hazards for landing spacecraft. The rock abundance varies in the near field from 0.6% for the sand and pebble‐rich area to the east within Homestead hollow to ∼3–5% for the progressively rockier areas to the south, north, and west. The rock abundance of the entire near field is just over 3%, which falls between that at the Phoenix (2%) and Spirit (5%) landing sites. Rocks in the far field (<40 m) that could be identified in both the surface panorama and a high‐resolution orbital image fall on the same exponential model curve as the average near‐field rocks. Rocks measured in a high‐resolution orbital image (27.5 cm/pixel) within ∼500 m of the lander that includes several rocky ejecta craters fall on 4–5% exponential model curves, similar to the northern and western near‐field areas. As a result, the rock abundances observed from orbit fall on the same exponential model rock abundance curves as those viewed from the surface. These rock abundance measurements around the lander are consistent with thermal imaging estimates over larger pixel areas as well as expectations from fragmentation theory of an impacted Amazonian/Hesperian lava flow. Key Points: Rocks measured within 10 m, 40 m, and ∼500 m of the InSight lander cover 0.6–5%, ∼3%, and 4–5% cumulative fractional area of the surface The rock size‐frequency distributions observed from the orbit and the surface are on similar exponential model curves Rock abundance at InSight is between the Phoenix and Spirit landing sites and is consistent with orbital thermal imaging estimates